Intra-household gender differences in Perception of climate change and adaptation strategies in Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The research has been completed and published in the International Journal of Climate Change Strategies and Management. Results from this research has been presented to several audiences (national and international)